Rapid age assessment of glacial landforms in the Pyrenees using Schmidt hammer exposure dating (SHED). Issue 1 (2nd April 2018) - Tomkins, Matt D.; Dortch, Jason M.; Hughes, Philip D.; Huck, Jonny J.; Stimson, Andrew G.; Delmas, Magali; Calvet, Marc; Pallàs, Raimon
Abstract: Schmidt hammer (SH) sampling of 54 10 Be-dated granite surfaces from the Pyrenees reveals a clear relationship between exposure and weathering through time (n=52, R 2 =0.96, P <0.01) and permits the use of the SH as a numerical dating tool. To test this 10 Be-SH calibration curve, 100 surfaces were sampled from five ice-front positions in the Têt catchment, eastern Pyrenees, with results verified against independent 10 Be and 14 C ages. Gaussian modelling differentiates Holocene (9.4±0.6 ka), Younger Dryas (12.6±0.9 ka), Oldest Dryas (16.1±0.5 ka), last glacial maximum (LGM; 24.8±0.9 ka) and Würmian maximum ice extent stages (MIE; 40.9±1.1 ka). These data confirm comparable glacier lengths during the LGM and MIE ( 300 m difference), in contrast to evidence from the western Pyrenees (≥15 km), reflecting the relative influence of Atlantic and Mediterranean climates. Moreover, Pyrenean glaciers advanced significantly during the LGM, with a local maximum at 25 ka, driven by growth of the Laurentide Ice Sheet, southward advection of the polar front, and a solar radiation minimum in the Northern Hemisphere. This calibration curve is available online (http://shed.earth ) to enable wider application of this method throughout the Pyrenees.